Nuevas y viejas quinolonas. - MAGUIÑA VARGAS, Ciro; SOLARI ZERPA, Lesly (Revista Médica Herediana, 2013)
Quinolones are a family of antibiotics of great importance in the management of several community and nosocomial diseases. Therefore, it is important to know the qualities of the old and new quinolones. Quinolones, as anti-infectious agents, are effective and safe and few times ocurrs adverse events. After 1962, when the first quinolon, nalidix acid, appeared, new generations of quinolones (fourth generation) have appeared in the market. However, we should know strictly its indications, most infectious diseases are the agents of elections, but in another cases, are drugs of second line. The objective of this review is to know better all quinolones in order to avoid the appearance of resistance due to its mal practice. In this review, we present pharmakocinetic aspects, currently indications of the fluorquinolones, the importance of new quinolones, the mechanisms of resistance, its contraindications and adverse events. ( Rev Med Hered 2002; 13: 153-160 ).